Strategy for Developing Human Resources for Teaching Personnel in the Maluku Islands Region - R. Kempa; A. Sahalessy; Elfridawati Mai Dhuhani (Postgraduate, University of Mataram, 2025)
The strategy for developing Human Resources (HR) for Teaching Staff in the Maluku Islands region is very interesting to discuss considering that this discussion has not been widely explained in scientific articles. The purpose of writing this article is to look at the strategy for developing HR for teaching staff in the Maluku Islands region. This writing uses a qualitative research method, with 3 people interviewed, namely the principal, the chairman of the Elementary and Middle Education Council of the Muhammadiyah Regional Leadership of West Seram Regency and teachers. The data collection techniques are in the form of interviews, documentation and observation. The data analysis technique is in the form of data verification, drawing conclusions. For the results of this study it was found that the development strategy (1) Training Sustainable: Workshops, online training, collaboration with higher education institutions. (2) Mentoring and Supervision: Collaboration with experienced teachers. (3) Use of Technology: E-learning and digital platforms for training. (4) Teacher Welfare: Incentives, and logistical support. The strategy for developing human resources for teaching staff in the island regions requires full support from various parties, including the government, schools, communities, and private organizations. With an integrated and sustainable approach, the challenges faced by teaching staff in remote areas can be overcome, so that the quality of education in the island regions can be improved.